Perancangan User Experience Aplikasi Pencarian Jasa Tutor Bimbingan Belajar menggunakan Metode Human-Centered Design - Alin Kinanti; Lutfi Fanani; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Tutoring is a form of mentoring students outside of school by a tutor. The purpose of tutoring is to improve the quality of learning. The educational background and busyness of parents are usually the reason parents need tutors for their children to study outside of school. The limitations of tutors in disseminating information about their services are the cause of the difficulty of parents getting tutors for their children so that students take a long time to overcome their difficulties in learning. Tutoring information is usually given by word of mouth. Information given by word of mouth is not effective because sometimes the information conveyed is inaccurate. From these problems, a solution is needed to help connect between parents and tutors. The research conducted aims to design an application for tutoring tutoring services to connect parents and tutors.design User experience is needed in this study so that the application is made according to user needs. The research was conducted using the Human-Centered Design method. The evaluation is carried out using Usability Testing and System Usability Scale (SUS) as a user satisfaction test tool.evaluation usability testing get a success rate of 100% and an error rate 0% and get an efficiency 0.145 goals/sec and 0.091 goals/sec. evaluation using SUS got a score of 78, which means it is included in grade B+.